ЕПІСТОЛЯРІЙ МИКОЛИ ГОГОЛЯ У СТУДІЮВАННІ КУЛІША-РОМАНТИКА - Свириденко О. М. (World Science, 2019)
The article reveals P. Kulish’s studies on M. Gogol. It is established, that the actualization of the letter correspondence genre at the time of Romanticism was determined by the whole complex of literary and non- literary causes. Here we point out to anthropocentrism of Romanticism literature, to the strengthening of the subjective origin in it, to the changes in the human concept and to the change of the artist concept (if we talk about publishing practice of Romantics) where a Romantic was proclaimed to martyr and demigod at the same time and it raised great interest to the writers’ epistolary. It is stated that P. Kulish’s interest to epistolary inheritance of M. Gogol was caused by typical romantic instructions according to which a letter was proclaimed as a priority source of studying addressee’s spiritual biography. Composing letters according to the chronological principle P. Kulish was directed by the aspiration to draw spiritual evolution of their author and that fully suited the publishing practice of Romantics.